Can the cardiovascular family history reported by our patients be trusted? The Norwegian Stroke in the Young Study. (21st August 2015) - Øygarden, H.; Fromm, A.; Sand, K. M.; Eide, G. E.; Thomassen, L.; Naess, H.; Waje‐Andreassen, U.
Abstract : Background and purpose: Family history (FH) is used as a marker for inherited risk. Using FH for this purpose requires the FH to reflect true disease in the family. The aim was to analyse the concordance between young and middle‐aged ischaemic stroke patients' reported FH of cardiovascular disease (CVD) with their parents' own reports. Methods: Ischaemic stroke patients aged 15–60 years and their eligible parents were interviewed using a standardized questionnaire. Information of own CVD and FH of CVD was registered. Concordance between patients and parents was tested by kappa statistics, sensitivity, specificity, predictive values and likelihood ratios. Regression analyses were performed to identify patient characteristics associated with non‐concordance of replies. Results: There was no difference in response rate between fathers and mothers ( P  = 0.355). Both parents responded in 57 cases. Concordance between patient and parent reports was good, with kappa values ranging from 0.57 to 0.7. The patient‐reported FH yielded positive predictive values of 75% or above and negative predictive values of 90% or higher. The positive likelihood ratios (LR+) were 10 or higher and negative likelihood ratios (LR−) were generally 0.5 or lower. Interpretation regarding peripheral arterial disease was limited due to low parental prevalence. Higher age was associated with impaired concordance between patient and parent reports (odds ratio 1.05; 95% confidence interval 1.01–1.09; P  = 0.020). Conclusions: The FH provided by young and middle‐aged stroke patients is in good concordance with parental reports. FH is an adequate proxy to assess inherited risk of CVD in young stroke patients.